2004
DOI: 10.1002/qsar.200420021
|View full text |Cite
|
Sign up to set email alerts
|

High Capacity Poly(ethylene glycol) Based Amino Polymers for Peptide and Organic Synthesis

Abstract: A beaded, chemically stable, high capacity amino resin for solid phase synthesis under polar and non-polar conditions is described. By exhaustive reduction of amide carbonyl groups in PEG cross linked poly(ethylene glycol)-poly(-acrylamide) copolymer (PEGA) a significant increase in functional amino groups is obtained. Furthermore, a resin containing 90% PEG which is free of amide carbonyl groups is produced. The polymer was characterized by IR spectroscopy and the macroscopic properties of the beads were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 29 publications
(8 reference statements)
0
82
0
6
Order By: Relevance
“…Another common way to analyze mechanical strength of particles with sizes down to 2 µm in diameter is via compressing a single particle between two plates and measuring the deformation [294][295][296][297] by several ways such as microscopy [298] or weighing [299]. This technique is more suitable for monodisperse spherical particles since the measurement is generally performed on a single particle.…”
Section: Mechanical Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Another common way to analyze mechanical strength of particles with sizes down to 2 µm in diameter is via compressing a single particle between two plates and measuring the deformation [294][295][296][297] by several ways such as microscopy [298] or weighing [299]. This technique is more suitable for monodisperse spherical particles since the measurement is generally performed on a single particle.…”
Section: Mechanical Strengthmentioning
confidence: 99%
“…Although there are numerous studies on CuAAC functionalization of nonporous polymers [280,298,328,[336][337][338][339][340][341][342][343][344][345][346][347][348][349][350][351], silica [352][353][354] and metal particles [355], the amount of publications on porous polymer particles is limited. Finn et al [356] described the click functionalization of a commercial porous agarose resin for affinity chromatography.…”
Section: Cu(i) Catalyzed Azide-alkyne Cycloaddition (Cuaac)mentioning
confidence: 99%
“…[26] In their studies, the linear peptide 21, in which the azide and alkyne group are introduced onto amino acid side chains, was synthesized by SPPS on a PEGA resin. Then, the intramolecular cyclization, catalyzed by CuI and DIPEA in THF, proceeded smoothly.…”
Section: Cyclization Of Peptides With Click Chemistrymentioning
confidence: 99%
“…Then, cleavage from the resin produced 76 % of the desired product. [26] A recent study demonstrated double cyclization with the simultaneous formation of two triazoles to mimic the two disulfide bonds in antibacterial bhairpin peptides. [42] The head-to-tail cyclization has frequently been complicated by dimerization and oligomerization.…”
Section: Cyclization Of Peptides With Click Chemistrymentioning
confidence: 99%
“…Na química de materiais, a reação "click" vem sendo extensivamente utilizada na obtenção de diversos materiais, tais como dendrí-meros, 37,38,[104][105][106][107] polímeros, [108][109][110][111] fases estacionárias modificadas, [119][120][121][122] organogéis, [123][124][125] macrociclos, [134][135][136] dentre outros. Dendrímeros são moléculas formadas a partir de um núcleo polifuncionalizado através do crescimento radial de camadas, de forma repetitiva.…”
Section: Química De Materiaisunclassified